Real-World Lab Data in Natalizumab Treated Multiple Sclerosis Patients Up to 6 Years Long-Term Follow Up - Kaufmann, Maxi; Haase, Rocco; Proschmann, Undine; Ziemssen, Tjalf; Akgün, Katja (Frontiers in Neurology, 2018)
Natalizumab inhibits the transmigration of immune cells across the blood-brain barrier thus inhibiting inflammation in the central nervous system. Generally, this blockade at the blood-brain barrier has significant influence on the circulating lymphocytes. Up to date, only short-term data on peripheral blood parameters are available which are mostly from controlled clinical trials and not from real-world experience. Real-world lab data of 120 patients diagnosed with highly active disease course of relapsing-remitting multiple sclerosis (RRMS) were analyzed. Patient sampling was performed by consecutive recruitment in the Multiple Sclerosis Center Dresden. Lab testing was performed before and every third infusion up to 72 months follow-up. After first natalizumab infusion, absolute numbers of all major lymphocyte populations including CD4+ T-cells, CD8+ T-cells, CD19+ B-cells and NK-cells significantly increased and remained stable during the whole observation period of 72 months. Upon lymphocyte subsets, CD19+ B-cells presented a disproportionate increase up to levels higher than normal level in most of the treated patients. Neutralizing antibodies to natalizumab abrogate the described changes. Intra-individual variation of lymphocytes and its subsets remained in a narrow range for the whole treatment period. CD4/CD8 ratio did not change compared to baseline measurement up to six years of natalizumab treatment. Monocytes, eosinophils and basophils, but not neutrophils persistently increased during natalizumab treatment. Hematological parameters including erythrocyte, platelet count, hemoglobin and hematocrit remained unchanged compared to baseline. Interestingly, immature precursor cells including erythroblasts were detectable in 36,8% of the treated patients during natalizumab therapy, but not in the pretreatment period. Asymptomatic elevations of liver enzymes were rare, mostly only transient and lower than 3x upper normal limit. Kidney function parameters remained stable within physiological ranges in most patients. CRP levels > 20mg/dl were recognized only in 10 patients during natalizumab therapy and were linked to respiratory tract infection. In order to improve decision-making and thus to optimize treatment management, analysis of real-world data is notably important. In our present analysis we reported persistent, but stable increases of peripheral immune cell subtypes in natalizumab treated patients. Additional serological analyses confirm excellent tolerability and safety even six years after natalizumab initiation in post-marketing experience.